Visible light communication with efficient far-red/near-infrared polymer light-emitting diodes - Minotto, Alessandro (Light Sci Appl, 2020)
Visible light communication (VLC) is a wireless technology that relies on optical intensity modulation and is potentially a game changer for internet-of-things (IoT) connectivity. However, VLC is hindered by the low penetration depth of visible light in non-transparent media. One solution is to extend operation into the “nearly (in)visible” near-infrared (NIR, 700–1000 nm) region, thus also enabling VLC in photonic bio-applications, considering the biological tissue NIR semitransparency, while conveniently retaining vestigial red emission to help check the link operativity by simple eye inspection. Here, we report new far-red/NIR organic light-emitting diodes (OLEDs) with a 650–800 nm emission range and external quantum efficiencies among the highest reported in this spectral range (>2.7%, with maximum radiance and luminance of 3.5 mW/cm(2) and 260 cd/m(2), respectively). With these OLEDs, we then demonstrate a “real-time” VLC setup achieving a data rate of 2.2 Mb/s, which satisfies the requirements for IoT and biosensing applications. These are the highest rates ever reported for an online unequalised VLC link based on solution-processed OLEDs.